PENGEMBANGAN EKONOMI KAWASAN PERBATASAN NEGARA DI KALIMANTAN BARAT - Edyanto, CB Herman (Badan Pengkajian dan Penerapan Teknologi, 2007)
International boundary between two state is an important place where the local resident’s activities are executed. The differences between two countries in the border area include several aspects such as national income per capita which about on frequently give different life colour also among frontier society and social education. The fact is that the social and economic life of Indonesian frontier society are more influenced by requirement and culture of society of Malaysia. The government of Indonesia nowadays attempts to be able to build national program and develop economic activities for frontier society in West Kalimantan Province among others establishing industries and work along with governmentof Malaysia